Application of biomarkers in the development of drugs intended for the treatment of osteoarthritis - Kraus, V.B.; Burnett, B.; Coindreau, J.; Cottrell, S.; Eyre, D.; Gendreau, M.; Gardiner, J.; Garnero, P.; Hardin, J.; Henrotin, Y.; Heinegård, D.; Ko, A.; et al. (Osteoarthritis and cartilage, 2011)
Osteoarthritis (OA) is a chronic and slowly progressive disease for which biomarkers may be able to provide a more rapid indication of therapeutic responses to therapy than is currently available; this could accelerate and facilitate OA drug discovery and development programs. The goal of this document is to provide a summary and guide to the application of in vitro (biochemical and other soluble) biomarkers in the development of drugs for OA and to outline and stimulate a research agenda that will further this goal. The Biomarkers Working Group representing experts in the field of OA biomarker research from both academia and industry developed this consensus document between 2007 and 2009 at the behest of the Osteoarthritis Research Society International Federal Drug Administration initiative (OARSI FDA initiative). This document summarizes definitions and classification systems for biomarkers, the current outcome measures used in OA clinical trials, applications and potential utility of biomarkers for development of OA therapeutics, the current state of qualification of OA-related biomarkers, pathways for biomarker qualification, critical needs to advance the use of biomarkers for drug development, recommendations regarding practices and clinical trials, and a research agenda to advance the science of OA-related biomarkers. Although many OA-related biomarkers are currently available they exist in various states of qualification and validation. The biomarkers that are likely to have the earliest beneficial impact on clinical trials fall into two general categories, those that will allow targeting of subjects most likely to either respond and/or progress (prognostic value) within a reasonable and manageable time frame for a clinical study (for instance within 1–2 years for an OA trial), and those that provide early feedback for preclinical decision-making and for trial organizers that a drug is having the desired biochemical effect. As in vitro biomarkers are increasingly investigated in the context of specific drug treatments, advances in the field can be expected that will lead to rapid expansion of the list of available biomarkers with increasing understanding of the molecular processes that they represent.